The Effect of Social Media Marketing on Purchase Decision: Fear of Missing Out as a Mediating Factor Among Gen Z Consumers - Rafli Indra (Brilliant International Journal Of Management And Tourism, 2026)
The rapid growth of digital technology has transformed consumer behavior, especially among Generation Z who are highly active on social media. One notable trend is the increasing purchase of branded tumblers, which function not only as utility products but also as symbols of lifestyle and identity. Social media marketing plays an important role in shaping this behavior, while psychological factors such as Fear of Missing Out (FoMO) further influence consumer decisions. This study aims to examine the effect of Social Media Marketing on Purchase Decision, the effect of Social Media Marketing on FoMO, the effect of FoMO on Purchase Decision, and the mediating role of FoMO in the relationship between Social Media Marketing and Purchase Decision. The research was conducted in Denpasar City using a quantitative approach with 110 Generation Z respondents. Data were analyzed using Partial Least Squares (PLS) with SmartPLS software. The results reveal that Social Media Marketing has a strong positive and significant effect on Purchase Decision, indicating that effective digital marketing strategies directly encourage consumers to purchase branded tumblers. In addition, Social Media Marketing also has a positive and significant effect on FoMO, while FoMO itself significantly influences Purchase Decision. Furthermore, FoMO is proven to positively and significantly mediate the relationship between Social Media Marketing and Purchase Decision. It is recommended that companies, particularly branded tumbler brands, improve the quality and informativeness of their social media content, strengthen interaction and engagement with consumers, and foster a stronger sense of community among users. In addition, the use of Fear of Missing Out (FoMO) in marketing strategies should be applied carefully and responsibly to maintain consumer trust and support long-term relationships.